The impact of the number of higher education institutions (HEIs) on the annual regional GDP per capita in Philippine regions - Garcia, Jaymich B.; Lobo, Kevin Michael Y.; Mendoza, Maria Nimfa F. (Quezon City School of Economics, University of the Philippines Diliman, 2018)
Several studies have shown that the presence of higher education institutions (HEIs) affects economic growth through the production of human capital, innovation and the quality of education being offered. Although being fourth (4th) in the world in terms of countries with most number of HEIs, the Philippines displayed a slower, stunted economic growth throughout the years. The purpose of this study is to assess and identify the specific contribution of the number of HEIs to the growth of Gross Domestic Product (GDP) per capita in the Philippine regions. Separate economic models are estimated by the researchers to evaluate both short and long run effects of HEIs to GDP per capita of Philippine regions. The study is limited from the year 2009 to 2017 due to data limitations. The pooled ordinary least squares model and the fixed effect model showed that having an additional HEI per region can increase annual real GDP per capita by .3 percent in the short-run while decreasing real GDP per capita by .2 percent in the long-run. Also, result shows that as one additional center of development or center of excellence (codcoe) translates to an annual 1.84 percent increase in real GDP per capita in a region. This further explains that quality as measured by the number of cod and coe per region affects GDP per capita more significantly than quantity of HEIs itself.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: Universities and colleges -- Economic aspects -- Philippines; Gross domestic product -- Philippines